cocoa, cocoa powder Determination of Cocoa Powder Production Quality in Small-Medium Enterprises Processing using Six Sigma Analysis - Hendy Firmanto (Coffee and Cocoa Research Journal, 2021)
Cocoa powder now has become a common craft product of small-medium enterprises (SME) processing in Indonesia. Small-medium enterprises develop processing sequence in smaller quantity compared to big company, nonetheless it must follow the national cocoa powder standard of SNI 3737:2009. The aim of this experiment was to evaluate the SME process production performance through Six Sigma analysis of the product to comply the standard requirements. The cocoa powder product was evaluated using three critical to quality (CTQ) parameters involving water content, color, and fineness. National standard determined of water content value is maximum 5%, the color is brown or Agtron number 65 and minimum finenesss percentage of particle (75 µm) must be 99.5%. This result explain the stability process of SME which is exceeding the control limit value of non conformity product. Its process capability showing the Sigma value of 2.6 with defect per million value was 126,667. The CTQ parameter which contribute to the high non-conformity are finenesss 78.95% and color 21.05%. The rough cocoa powder or finenesss affects the highest non-conformity related to the high fat content in cocoa cake as input process and can be revised by upgrading the pressing machine performance.